A great wave: the Storegga tsunami and the end of Doggerland?. (December 2020) - Walker, James; Gaffney, Vincent; Fitch, Simon; Muru, Merle; Fraser, Andrew; Bates, Martin; Bates, Richard
Abstract: Abstract : Around 8150 BP, the Storegga tsunami struck North-west Europe. The size of this wave has led many to assume that it had a devastating impact upon contemporaneous Mesolithic communities, including the final inundation of Doggerland, the now submerged Mesolithic North Sea landscape. Here, the authors present the first evidence of the tsunami from the southern North Sea, and suggest that traditional notions of a catastrophically destructive event may need rethinking. In providing a more nuanced interpretation by incorporating the role of local topographic variation within the study of the Storegga event, we are better placed to understand the impact of such dramatic occurrences and their larger significance in settlement studies.